Selective Histone Deacetylase Inhibitors with Anticancer Activity - Ma, Nan; Luo, Ying; Wang, Ying; Liao, Chenzhong; Ye, Wen-Cai; Jiang, Sheng (Current Topics in Medicinal Chemistry, 2016)
HDAC inhibitors (HDACIs), which can be used to kill cancer cells through inhibiting histone deacetylase activity or altering the structure of chromatin, have emerged as efficacious agents in the treatment of cancer. With SAHA, FK228, belinostat and panobinostat approved by the FDA, displaying satisfying activity in both haematological and solid tumors of various tissues, efforts to create selective HDACIs have been attracted attention over the past several years. Herein, we mainly review the progress of selective HDAC inhibitors including class-selective and isoform-selective HDAC inhibitors.
Keywords: Class III